On the synthesis and characterization of all-silica CHA zeolite particles - Kim, Eunjoo; Lee, Maro; Baik, Hionsuck; Han, Doug-Young; Ha, Jeong-Myeong; Choi, Jungkyu (ELSEVIER SCIENCE BV, 2014)
Mono-dispersed anisometric zeolite particles are desirable for forming a uniform, oriented layer. The epitaxial growth of this uniform layer is expected to provide an easier method for manufacturing continuous, oriented zeolite films than other approaches, including in situ methods. However, the inhomogeneous environment of the solid-like precursor required for the synthesis of all-silica CHA (Si-CHA) zeolites impedes the formation of mono-dispersed Si-CHA particles; instead, the precursor generally produces nearly cubic Si-CHA particles with a wide size distribution (similar to 1-10 mu m). Accordingly, elucidation of the effects of synthetic conditions on size distribution, morphology, and crystal-phase formation or transition of Si-CHA zeolites is necessary to achieve desired Si-CHA particles. In this study, the reaction temperature, molar composition, and synthesis time were systematically varied to investigate their effects on the resultant Si-CHA particles. Along with the nearly cubic Si-CHA particles, plate-like Si-CHA particles, which are promising for forming a uniformly oriented layer, were found to be synthesized as a minor product. The H2O/SiO2 molar ratio, which was less than similar to 3 in the synthesis precursor, was key to the co-synthesis of plate-like Si-CHA particles. The plate-like Si-CHA particles could be observed by SEM and indirectly confirmed via selective deposition. Thermogravimetric analysis effectively recognized the minor presence of the plate-like Si-CHA particles presumably due to the shorter pathways for template removal during calcination. Though considerably minor, EAB-like particles, which were possibly generated due to a fault in stacking sequence, were discovered in addition to the above-mentioned nearly cubic and plate-like Si-CHA particles. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: GAS SEPARATION; SAPO-34 MEMBRANES; MOLECULAR-SIEVES; FLUORIDE MEDIA; ADSORPTION; DDR; CO2; PERMEATION; MIXTURES; PERFORMANCE